The effects of autologous platelet concentrate on the healing of intra-bony defects: a randomized clinical trial - Nilofar Attar; Aashima Gupta; Nabeeh A. Alqahtani̇; Shahab Saquib Abullai̇s; Nitin Dani̇; Nitin Kudyar (Istanbul University, 2019)
PurposeThe present study aimed to evaluate the clinical and radiographic effects ofautologous platelet concentrate (APC) on the healing of intra-bony defects filledwith β-tricalcium phosphate (β-TCP) and covered with collagen membranes.Subjects and methodsThis study included 30 defects of 14 systemically healthy subjects. All of them had,at least, two deep intra-bony, inter-proximal periodontal defects. Minimum probingpocket depth (PPD) was 6 mm. Clinical and imaging examination was performedboth at baseline and at 3, 6, and 9 months after surgery.ResultsBoth the test and control group revealed a significant reduction in all variableswhen compared with the base line. Mean reduction of the PPD in two groups ateach follow-up time point showed no significant difference. Means of the clinicalattachment gain of the same groups were significantly different (p<0.05). Meangingival recession at 3 month was not significant. However, the means of gingivalrecession coverage of two groups were significantly different at 6 and 9 months(p<0.05 for both).ConclusionSites treated with APC are more likely to demonstrate more clinical attachment gainand recession coverage at the end of 9 month compared to those without APC.